The ‘Engine’ And ‘Fuel’ of Carbon Financing: Carbon Markets And Offsetting Mechanisms In The Post-Paris Era – A Bibliometric Analysis. - Muchiri, Martin Kamau; Erdei-Gally, Szilvia; Fekete-Farkas, Maria (Acta Carolus Robertus, 2025)
The study aimed to provide a one-stop overview of research regarding carbon financing through carbon markets and offsetting mechanisms through a comprehensive bibliometric analysis. The dataset was derived from the Web of Science and analyzed using the biblioshiny package available in R, Vos viewer software, and Microsoft Excel. The study summarizes results on the main details of the corpus used, trend patterns, thematic topics, co-citation performance, and co-occurrences. The study reveals valuable insights, including a conspicuous research gap within the African region. China is identified as the most dominant country regarding research related to carbon financing and carbon credit trading. There is evidence of regional and inter-regional research collaborations between continents and countries, especially within Asia, Europe, and North America. The study recommends strengthening research collaborations with African countries as well as exploring emerging themes such as carbon sequestration, blue carbon initiatives, and the application of game theory in driving carbon financing innovations. Regarding research limitations, the scope of the analysis is limited to one database i.e., the Web of Science, and results might be geographically biased as there is a high absence of research contributions from Africa.
Keywords: Carbon financing; carbon markets; offsetting mechanisms; VOS Viewer; R